Skulptur von Wanamera (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Africa; Art; Artists; Sculpture; Yoruba Art; Papua New Guinea; New Guinea; Wood Sculpture